Systematic review on educational implications of ASD and ADHD comorbidity - Rico-Moreno, Jennifer; Tárraga-Mínguez, Raúl (Anales de Psicología / Annals of Psychology, 2016)
The recent publication of DSM-5, introduces as novelty to accept the comorbidity between the Attention Deficit/Hyperactivity Disorder (ADHD) and the Autism Spectrum Disorder (ASD). This article reviews previous researches that have study this comorbidity. A total of 40 investigations were reviewed, establishing 7 different themes. The results of this review showed that the presence of ADHD in ASD increased the severity of autistic symptoms and that its comorbidity was associated with higher rates of disruptive behaviors, parental stress, poorer quality of life and poor social skills.